Direct Observation of the Radial Magnetic Field Gradient in HD 58260 from Spectropolarimetry of NLTE Lines in Emission - Giarrusso, Marina (The Astrophysical journal, 2022)
Because of the unquestionable presence of magnetic fields in stars, their role in the structure of stellar atmospheres has for a long time been a subject of speculation. In our contribution to this discussion we present spectropolarimetric evidence of the decrease of the radial component of the magnetic field with altitude in the atmosphere of HD 58260, a B-type magnetic star on the main sequence. We show that the Stokes V profiles of metal lines in emission of the outer atmosphere are evidence for a field three times weaker than absorption lines from inner layers. The extra flow of energetic particles due to the magnetic-gradient pumping mechanism could be at the origin of the magnetospheres surrounding this class of stars and at the basis of the high-energy phenomena observed. We also list a series of spectral lines useful for measuring the surface field of early-type stars.